Bilans ChZT w biologicznym oczyszczaniu ścieków osadem czynnym - cz. 2. badania w skali technicznej = COD balance in biological treatment of wastewater - part 2. technical scale - Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article the balance of COD for wastwater treatment plant in Sulechow was prepared. The theoretical bases of COD balancing and the ex-ample calculations were in the work "COD balance in biological treat-ment of wastewater - part 1 - laboratory scale" described.
Keywords: bilans ChZT; osad czynny; strata węgla organicznego; balance of COD; "loss" organic carbon; activated sewage sludge